DESCRIPTION OF BREAKFAST HABITS AND SLEEP DURATION IN OVER NUTRITION ADOLESCENTS AT SMP MUHAMMADIYAH LIMBUNG GOWA DISTRICT - Nahda Fadhilah; Abdul Salam; Laksmi Trisasmita; Nurhaedar Jafar; Marini Amalia Mansur (Ikatan Sarjana Gizi Indonesia (ISAGI), 2023)
Introduction: One of the nutritional problems that often occurs in the adolescent environment is the phenomenon of overweight and obesity. One of the factors that can cause overnutrition in adolescents is the habit of skipping breakfast and sleep duration. Objective: This study aims to determine the description of breakfast habits and sleep duration in adolescents with overweight status at SMP Muhammadiyah Limbung, Gowa Regency. Methods: This study used a descriptive design. The research sample was adolescents aged 13-15 years in classes VII and VIII who were overweight. The sample determination used total sampling with a total sample of 79 people. Breakfast habits and breakfast quality were obtained through an interview questionnaire and 24-hour recall, and sleep duration was obtained through the Sleep Timing Questionnaire (STQ). Results: Most respondents had a habit of rarely having breakfast <4 times/week (64.5%) and still had poor breakfast quality which was <15% of the RDA (50.6%). Sleep duration of most adolescents was <8 hours/day both weekdays (58.2) and weekends (51.9%). Conclusion: Most of the overnourished adolescents at SMP Muhammadiyah Limbung have a habit of rarely eating breakfast and the quality of breakfast is still lacking. The duration of sleep of most adolescents is still lacking, namely <8 hours / day both weekdays and weekends.